2008
DOI: 10.1146/annurev.biochem.75.101304.124125
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Protein Profiling: From Enzyme Chemistry to Proteomic Chemistry

Abstract: Genome sequencing projects have provided researchers with a complete inventory of the predicted proteins produced by eukaryotic and prokaryotic organisms. Assignment of functions to these proteins represents one of the principal challenges for the field of proteomics. Activity-based protein profiling (ABPP) has emerged as a powerful chemical proteomic strategy to characterize enzyme function directly in native biological systems on a global scale. Here, we review the basic technology of ABPP, the enzyme classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1,047
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 1,107 publications
(1,081 citation statements)
references
References 153 publications
3
1,047
0
14
Order By: Relevance
“…In this study, we revealed that vibsanin B preferentially targets HSP90b and has a very weak binding with HSP90a through activity-based protein profiling method (40), indicating that inhibition of HSP90b, but not HSP90a, would be mainly responsible for the inhibitory effect of vibsanin B on leukocyte migration. Because of high conservation in sequence, the function of HSP90a and HSP90b is very similar (41), although previous work reported that HSP90a, but not HSP90b, exerts an essential extracellular role in cancer cell invasiveness (42).…”
Section: Discussionmentioning
confidence: 84%
“…In this study, we revealed that vibsanin B preferentially targets HSP90b and has a very weak binding with HSP90a through activity-based protein profiling method (40), indicating that inhibition of HSP90b, but not HSP90a, would be mainly responsible for the inhibitory effect of vibsanin B on leukocyte migration. Because of high conservation in sequence, the function of HSP90a and HSP90b is very similar (41), although previous work reported that HSP90a, but not HSP90b, exerts an essential extracellular role in cancer cell invasiveness (42).…”
Section: Discussionmentioning
confidence: 84%
“…Developing a gel-free sample processing workflow with on-bead enzymatic digestion of proteins would make identification of suicide inhibitor targets tractable (32,33) and would be more amenable to automation. Although analytical throughput was not the primary focus of our studies, our current implementation of SILAC-Target I.D.…”
Section: Discussionmentioning
confidence: 99%
“…This latter knowledge can be obtained by using activity-based profiling of kinases 68 After labelling, affinity techniques were used to isolate 85 biotin-labelled proteins or peptides for identification and quantification through MS-based techniques. This approach was also used to determine the selectivity of protein kinase inhibitors towards a given protein kinase through competition studies 13 .…”
Section: E Activity-based Profiling Of Active Protein Kinasesmentioning
confidence: 99%